2016
DOI: 10.3390/e18020050
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation and Natural Convection of CuO-Water Nanofluid in C-Shaped Cavity under Magnetic Field

Abstract: This paper investigates the entropy generation and natural convection inside a C-shaped cavity filled with CuO-water nanofluid and subjected to a uniform magnetic field. The Brownian motion effect is considered in predicting the nanofluid properties. The governing equations are solved using the finite volume method with the SIMPLE (Semi-Implicit Method for Pressure Linked Equations) algorithm. The studied parameters are the Rayleigh number (1000 ď Ra ď 15,000), Hartman number (0 ď Ha ď 45), nanofluid volume fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(50 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Such irreversibilities may be caused by heat transfer across the finite temperature gradient, viscous dissipation and magnetic field effects, etc. The magnetic field influence on entropy generation in nanofluid-filled cavities has been exposed in the recent literature [26][27][28]. The results showed that the magnetic field and the presence of nanoparticle had a substantial influence on flow pattern, heat transfer, and entropy generation.…”
Section: Introductionmentioning
confidence: 89%
“…Such irreversibilities may be caused by heat transfer across the finite temperature gradient, viscous dissipation and magnetic field effects, etc. The magnetic field influence on entropy generation in nanofluid-filled cavities has been exposed in the recent literature [26][27][28]. The results showed that the magnetic field and the presence of nanoparticle had a substantial influence on flow pattern, heat transfer, and entropy generation.…”
Section: Introductionmentioning
confidence: 89%
“…The criterion of thermal performance against the generation of entropy that was proposed in past papers [36,37] is defined here in an inverse form as:…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Following Bejan's conclusions from these books, several studies have been published in this topic under different engineering circumstances. An analysis of entropy generation in enclosures with and without a nanofluid can be found in several past studies [29][30][31][32][33][34][35][36][37]. These studies recorded an increase in entropy generation with an increasing ratio of inertial to viscous forces, while there was conflict between heat transfer irreversibility and the volume fraction of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Prototypical structure of heat transfer procedure in various industries is acquired with an accurate measurement of entropy generation since it clarifies waste of energy in a process. Hence, entropy generation is examined into mixed convection of pure and nanofluid [28,29,30,31,32,33,34,35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%